2011
DOI: 10.1203/pdr.0b013e31820b9365
|View full text |Cite
|
Sign up to set email alerts
|

Linkage and Association Study of Neurotrophins and Their Receptors as Novel Susceptibility Genes for Childhood IgA Nephropathy

Abstract: Neurotrophins (NTs) and their receptors (NTRs) are known to be important for pathogenesis of various inflammatory diseases that occur in not only neuronal but also nonneuronal tissues, including kidney. Here, we investigated association between childhood IgA nephropathy (IgAN) and single nucleotide polymorphisms (SNPs) of genes encoding NTs [nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF)] and NTRs [nerve growth factor receptor (NGFR) and neurotrophic tyrosine kinase receptor 1-3 (NTRK1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The first two pathways had already been well studied and validated. 26,30 In our study, we chose the latter two which have less literature support and have inconsistent results to GSEA for experimental validation. Wnt signaling was reported as a dysregulated process in CARNIVAL and is known to be involved in podocyte injury and renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The first two pathways had already been well studied and validated. 26,30 In our study, we chose the latter two which have less literature support and have inconsistent results to GSEA for experimental validation. Wnt signaling was reported as a dysregulated process in CARNIVAL and is known to be involved in podocyte injury and renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the variant alters NGF gene expression (Akkad et al, 2008, Hahn et al, 2011, in the context of viral liver diseases, it is proposed that negative gene maintenance be detrimental to organ tissue integrity in the most advanced aggression profiles, which underscores the importance of NGF in controlling liver damage. In fact, in experimentally intoxicated mice, it has been shown that NGF expression by hepatocytes is directly regulated in areas of tissue regeneration during aggression (Oakley et al, 2003) (which in humans is a characteristic maintained in the advanced fibrosis stage) being pointed as a potential determinant in the resolution of the fibrotic response (Amoras et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The -198C > T polymorphism (rs11102930) located in the promoter region of the NGF gene has been associated with multiple sclerosis (Akkad et al, 2008), childhood IgA neuropathy (Hahn et al, 2011) and asthmatic disease (Szczepankiewicz et al, 2012). These studies propose that substitution of cytosine with thymine in that specific position (nt − 198) modifies the binding site for transcription factors such as vitamin D receptor (VDR) and specificity protein 1 (Sp1), which in turn alters NGF expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotrophins and receptors are involved in different events to ensure the correct functioning of the kidney, such as growth, differentiation, and regulation of renal tubule transport. Indeed, recent functional in vivo studies, in mice models and in vitro in human patients, have revealed a close association between neurotrophin/receptor pathways and kidney diseases [27][28][29]. However, further studies using emerging animal models [30], such as zebrafish (Danio rerio), could be useful to elucidate the specific mechanisms of these pathologies.…”
Section: Introductionmentioning
confidence: 99%